Integration of 5S Values (Seiri, Seiton, Seiketsu, Seiso, and Shitsuke) as a Character Development Strategy for the Performance of Indonesian Migrant Workers - Risda, Dianni; Syihabuddin, Syihabuddin; Nurdin , Encep Syarief; Malihah, Elly; Soon-hyeong, Lee (Universitas Negeri Semarang, 2025)
Vocational training institution as non-formal educational institutions play a role in providing job training to prospective migrant workers who will work abroad. The formation of work character in shaping the performance character of prospective migrant workers to meet the standards, ethos, and work culture in accordance with the demands of the global industry. This study aims to analyze the performance character development strategy by vocational training institutions for prospective Indonesian migrant workers who will work in Japan. Using a qualitative approach with the grounded theory method, the study was conducted at three different vocational training institution in Lingua Global Utama, Palapa Muda Indonesia and Puspa Setya Abadi. Data collection used in-depth interviews, observations, and documentation studies, and was analyzed using coding techniques consisting of open coding, axial coding, and selective coding. The findings show that, the work character development carried out by vocational training institutions in sending prospective migrant workers to Japan integrates the 5S principles (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) as both theoretical and practical learning. The 5S principles become the basis for performance character which is carried out with a contextual approach based on the reality of Japanese work culture collaborated with an experiential learning approach. The implication of the research is that the strategy for developing performance character based on the 5S principles in preparing prospective migrant workers needs to develop technical competencies supported by strengthening cross-cultural competencies.